Comprehensive evaluation approach of regional management for oil and gas stations and its application - Yong SUN; Zhaoyang LIU; Qiujuan LI; Zebin YOU; Yongjun CAI; Miao HE; Yu DIAO; Benben SHI (You-qi chuyun)
Objective With the continuous evolution of pipeline technologies, the regional management mode has emerged as an inevitable choice for the development of the long-distance oil and gas pipeline industry. To further advance regional management of oil and gas stations, enhancing risk control capabilities and delineating the advantages and disadvantages at various management levels during this transition process becomes imperative. Methods This paper presents a comprehensive evaluation system of regional management for oil and gas stations, utilizing the Layer of Protection Analysis (LOPA) within the process industry sphere. This approach integrates multiple evaluation techniques like expert scoring and hierarchical analysis, focusing on centralized monitoring, control, and maintenance to enhance risk management and control capabilities within operational zones. Results The proposed comprehensive evaluation system of regional management was applied to 10 typical oil and gas stations, leading to the effective identification of deficiencies in multiple aspects, including technical foundations, management systems, and staff competencies in operations and maintenance. These shortcomings were categorized into 31 specific concerns across 9 categories. The specific setbacks include the following: (1) The technical conditions for centralized control and monitoring, and reliability assessment fall short of requirements after the transformation of these oil and gas stations. (2) Some management regulations necessitate improvements, particularly those related to dispatching offices and operation areas, as well as maintenance teams in terms of their responsibilities, centralized patrol inspection, and maintenance. The enforcement and implementation of these documents need to be further reinforced. (3) Working staff capabilities at these oil and gas stations require improvement, and labor organization structures need further optimization. Conclusion The comprehensive evaluation of regional management assisted these oil and gas stations in uncovering shortcomings, identifying gaps, devising solutions, strengthening foundations, and fostering improvements. The evaluation outcomes provided them with systematic guidance and technical support in a unified, quantifiable, and graded manner, facilitating further progress in regional management.